AKSESIBILITAS JAMINAN KESEHATAN BAGI PEKERJA INFORMAL DI INDONESIA: ANALISIS KEBIJAKAN JAMINAN KESEHATAN NASIONAL BERDASARKAN PRINSIP HAK ASASI MANUSIA - Hanafi Hanafi; Istiana Heriani (Al-Adl : Jurnal Hukum, 2026)
The right to health is a fundamental right guaranteed under Article 28H of the 1945 Constitution of the Republic of Indonesia and various international human rights instruments, which obligate the state to provide health services that are available, affordable, accessible, and of adequate quality. In pursuit of this obligation, the Indonesian government launched the National Health Insurance Program (Jaminan Kesehatan Nasional/JKN), administered by BPJS Kesehatan, as part of the mandate of the National Social Security System Law. The program aims to deliver comprehensive health protection to all citizens, including informal workers, who account for more than 59% of the total working population in Indonesia. However, from a normative perspective, JKN policies have not fully accommodated the characteristics and needs of informal workers. The existing legal framework remains general in nature and has yet to provide specific regulations that are adaptive to the conditions of workers with unstable incomes, high mobility, and limited access to information. This situation has implications for low participation rates, the potential discontinuity of membership during income fluctuations, and disparities in access to health services. These conditions indicate a misalignment between the principle of universality mandated by regulation and the realities on the ground, resulting in unequal protection between formal and informal workers, as well as between urban and rural populations. Through a normative legal approach employing statutory and conceptual analyses, this study finds that strategic measures are required, including more flexible JKN financing schemes, the expansion of Contribution Assistance Recipients (Penerima Bantuan Iuran/PBI), the integration of participant data, the strengthening of primary healthcare facilities in remote areas, and the involvement of informal workers in the policy formulation process. These measures are expected to enhance the protection of the right to health for informal workers in an inclusive, equitable, and sustainable manner.